The Integration of MALL to Enhance Students Speaking Skill: An Autonomous Learning Model - Nafisatul Lutfi (Universitas Muhammadiyah Yogyakarta, 2020)
Mobile-Assisted Language Learning (MALL) is a new approach for students to learn language through the use of mobile technology. Learning a language should not only happen in a class setting activity but also happen outside the class in which the students take charge of their learning. Hence, it requires students' autonomy in learning the language. Students are now able to carry out their learning without depending on the teachers, which then leads to a sustainable and independent learning process. Quizlet, a web application, is introduced in this paper as an alternative solution to improve students’ speaking skill through an autonomous language learning activity. This paper used an action research method combined with a questionnaire to analyze the implementation of Quizlet in an autonomous class setting at STMIK AKAKOM Yogyakarta. The practical, usability, and sustainability aspects become the focus of this research. The data gathered from the action research shows that an autonomous learning activity still requires teachers to be the facilitator, and the questionnaire shows positive feedback from the students regarding the usability and sustainability of their language learning using the application.